Hall and Colman's diseases of the ear, nose and throat. - Burton, Martin; Leighton, Susanna; Robson, Andrew, 1961-; Russell, John, otolaryngologist; Colman, Bernard H. (Churchill Livingstone, 2000)
A radical rewrite of a famous and popular textbook on ENT, aimed at medical students and surgical trainees. Each section contains a succinct account of the relevant anatomy, full discussion of the examination of each region and complete coverage of both ENT surgery and disease.